2017
DOI: 10.1038/srep45693
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consumption of sugar-sweetened beverage during the growth period promotes social aggression in adult mice with proinflammatory responses in the brain

Abstract: Overconsumption of sugar-sweetened beverages (SSBs) is known to be a key contributor to the obesity epidemic; however, its effects on behavioral changes are yet to be fully studied. In the present study, we examined the long-term effects of SSB on social aggression in mice. Three-week-old weaned mice started to drink either a 30 w/v% sucrose solution (S30), plain water (CT), or an aspartame solution with sweetness equivalent to the sucrose solution (A30) and continued to drink until they were 11-week-old adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Given that sweet beverage consumption has been associated with social behavior dysfunctions [21], we next examined the social behavior of adult animals exposed or not to sucrose during adolescence and the impact of imipramine. Animals exposed to sucrose during adolescence did not exhibit significant changes in the time spent in social interaction and imipramine did not significantly affect social behavior ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that sweet beverage consumption has been associated with social behavior dysfunctions [21], we next examined the social behavior of adult animals exposed or not to sucrose during adolescence and the impact of imipramine. Animals exposed to sucrose during adolescence did not exhibit significant changes in the time spent in social interaction and imipramine did not significantly affect social behavior ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For microarray hybridization, total RNA was isolated and purified using a DNA-free RNA isolation kit (RNAqueous-4PCR kit; Ambion, Austin, TX, USA) according to the manufacturer's instructions. RNA samples were first amplified for array analysis using the Illumina Total Prep RNA Amplification Kit (Ambion) as previously described (29). Amplified cRNA (1.5 µg) was hybridized on Mouse WG-6 v2 Expression BeadChip arrays (Illumina Inc., San Diego, CA, USA), containing more than 45,281 well-annotated Ref transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…Gene set enrichment analysis (GSEA) was performed to examine the significance of the enrichment of the biological subsets of interest in the whole gene expression profiles (http://www.broadinstitute.org/gsea/index.jsp). Hierarchical clustering analysis was performed with Genesis software v1.7.5 using the Pearson correlation distance matrix with average linkage algorithm (29). Significant pathways were analyzed by the tools in Ingenuity ® Pathway Analysis (QIAGEN, Redwood City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Arcego et al ( 2016 ) demonstrated that rats exposed to 7 days of social isolation showed memory impairment and reduced BDNF, Na+, K+, ATPase activity, MAPK, AKT and phospho-AKT levels in PFCx; however, rats exposed to this stress situation but fed with HFD showed restored memory impairment as well as the aforementioned biochemical alterations. However, Choi et al ( 2017 ) demonstrated that sugar-sweetened beverages consumed by young mice significantly promoted social aggression in the adult life, which represents one of the most detrimental long-term outcomes of neurodevelopmental disorders (Lesch et al, 2012 ). Maged1-deficient mice (MAGE family genes, related with Prader-Willi syndrome (PWS), which includes hyperphagia, repetitive and compulsive behaviors, and cognitive impairment) developed progressive obesity associated with hyperphagia and a complex behavioral syndrome including reduced social interactions, memory impairments, deficient sexual behaviors, as well as increased anxiety, suggesting a connection between metabolic and behavioral outcomes (Dombret et al, 2012 ).…”
Section: Effects Of Obesity On Cognitive Functions and Moodmentioning
confidence: 99%